Spermatocytic seminoma associated with undifferentiated sarcoma: A rare case report - Priti Trivedi; Sunil Pasricha; Anuja Gupta (Wolters Kluwer Medknow Publications, 2011)
The presence of sarcomatous element transforms the usually innocuous spermatocytic seminoma into a highly aggressive neoplasm. We report a case of spermatocytic seminoma with undifferentiated sarcomatous component in a 43-year-old male, presented with testicular mass since two and a half years. Orchidectomy was performed and after 9 months, the patient presented with recurrent scrotal mass with bilateral pulmonary metastases.